Fracture toughness of nanofillers modified epoxy adhesives - Lim, Jarrod Hui Feng. (2011)
Epoxy has been widely used by engineers all over the world due to their outstanding mechanical properties. Applications of epoxy include adhesives, paints and coatings, structural matrix materials in aerospace application, of which epoxy adhesives will be the main study in this project.